Draft Twelfth Five Year Plan 2012-2017 and Annual Plan 2012-2013 Physical Targets and Achievements Volume-II B Government of Madhya Pradesh - Planning Commission (Planning Commission, 2012)
XIIth Plan 2007-12 Physical Targets & Achievement Physical Targets & Actual Achievement For Annual Plan 2010-11 Physical Targets and Anticipated Achievement For Annual Plan 2011-12 XIIth Plan 2012-17 & Annual Plan 2012-13 Proposed Physical Targets.
Government of Madhya Pradesh, Planning, Economics and Statistics Department